Discussion of ?Physio-chemical properties, consolidation, and stabilization of tropical peat soil using traditional soil additives ? a state of the art literature review? by Afnan Ahmad, Muslich Hartadi Sutanto, Mohammed Ali Mohammed Al-Bared, Indra Sati Hamonangan Harahap, Seyed Vahid Alavi Nezhad Khalil Abad, Mudassir Ali Khan - O'Kelly, Brendan (My University, 2022)
This discussion article provides commenting on the sections of the review paper by Ahmad et al. (the authors) concerning consistency limits determinations for peats and peaty soils, drawing on the writer’s experiences regarding the usefulness of liquid limit (LL) and plastic limit (PL) testing/results for these soils in explaining their geotechnical behaviors/properties. From the writer’s experience, despite being regularly specified in geotechnical engineering practice and used in research work, the conventional consistency limits tests generally do not produce physically meaningful results when testing peat soils, especially for more fibrous peats. Hence, the writer does not agree with the authors’ recommendations on consistency limits testing of peats; namely, they recommended that an utmost effort is needed to improve the quality and standard of the thread rolling test and the fall-cone test for consistency limits determinations of highly organic soils such as peat. Rather than grappling with various known inherent shortcomings of consistency limits testing for peats and other highly organic soils, a suggested way forward for assessing the likely geoengineering behavior/properties of these materials points to the routine measurement of a more useful suite of index tests; namely, their natural water content, organic content, fiber content, and humification (decomposition) level. In this discussion, the above aspects are explored in detail, including greater elaboration of the writer’s earlier research work in this area, which was touched on in the authors’ paper.
PUBLISHED
Keywords: Atterberg limits; Fibrous peat; Liquid limit; Organic soil; Plastic limit; Soil plasticity; Smart & Sustainable Planet; Atterberg limits; Environmental Geotechnics; GEOTECHNICAL ENGINEERING; Geotechnics; Organic soil; PEAT; PEAT SOILS; Plastic limit; Soil Mechanics; Soil Mechanics & Foundations; geotechnical; liquid limit; soil classification; soil plasticity